MR Angiography of Dural Arteriovenous Fistulas: Diagnosis and Follow-Up after Treatment Using a Time-Resolved 3D Contrast-Enhanced Technique - Meckel, S.; Maier, M.; Ruiz, D. San Millan; Yilmaz, H.; Scheffler, K.; Radue, E.-W.; Wetzel, S.G. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Digital subtraction angiography (DSA) is the method of reference for imaging of dural arteriovenous fistula (DAVF). The goal of this study was to analyze the value of different MR images including 3D contrast-enhanced MR angiography (MRA) with a high temporal resolution in diagnostic and follow-up imaging of DAVFs.MATERIALS AND METHODS: A total of 18 MR/MRA examinations from 14 patients with untreated (n = 9) and/or treated (n = 9) DAVFs were evaluated. Two observers assessed all MR and MRA investigations for signs indicating the presence of a DAVF, for fistula characteristics such as fistula grading, location of fistulous point, and fistula obliteration after treatment. All results were compared with DSA findings.RESULTS: On time-resolved 3D contrast-enhanced (TR 3D) MRA, the side and presence of all patent fistulas (n = 13) were correctly indicated, and no false-positive findings were observed in occluded DAVFs (n = 5). Grading of fistulas with this imaging technique was correct in 77% and 85% of patent fistulas for both readers, respectively. On T2-weighted images, signs indicative of a DAVF were encountered only in fistulas with cortical venous reflux (56%), whereas on 3D time-of-flight (TOF) MRA, most fistulas (88%) were correctly detected. In complete fistula occlusion, false-positive findings were encountered on both T2-weighted images and on TOF MRA images.CONCLUSION: In this study, TR 3D MRA proved reliable in detecting DAVFs and suitable for follow-up imaging. The technique allowed—within limitations—to grade DAVFs. Although 3D TOF MRA can depict signs of DAVFs, its value for follow-up imaging is limited.